A Book Critique of Introduction to Iranian Crafts Workshops - Samira Arab; Seyyed Abdul Majid Sharifzade (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
It is difficult to speak and theoretically analyze the handicrafts, although it may sound easy. Crafts are a familiar and tangible thing in everyday life, so it would be obvious without any need to know and try to understand them. The book “Introduction to Iranian Crafts Workshops” was compiled by Fariba Mostafavi in Mehr Nowruz Publications in 2016. Although the book is generally a collection of invaluable high-quality illustrations to introduce to some handicraft workshops, like any scholarly work, it has some formative and content deficiencies that have been attempted to criticize it critically. This research has explained the relevance of the library to some non-scientific propositions that mislead the reader (artists) and move from one research to another. In this regard, the following shortcomings and critical comments will be expressed in each of the following issues.